Does the Physical Type of House Still Affect Household Poverty in Indonesia? An Entropy-based Fuzzy Weighted Logistic Regression Approach (Journal of Information and Communication Technology, 2023)
Poverty is one of the biggest challenges facing the world nowadays. Numerous studies have concentrated on the characteristics thatdetermine poverty to identify poor households. One of the most important factors is the physical type of the house. The physical typeof houses includes floor type, wall type, roof type, and floor area per inhabitant in Indonesia, especially Surabaya, one of Indonesia’s bigcities and the capital of East Java Province. This factor gave promising results to the country. Therefore, it was assumed that these variablescould no longer distinguish between those in wealth and those in poverty. Poor household data are one example of imbalanced data interms of classification, which is a concern. The Rare Event Weighted Logistic Regression (RE-WLR) and Entropy-based Fuzzy Weighted Logistic Regression (EFWLR) methods were utilised to overcome these problems. As a result, the only factor, including the physical design of a house, which had a substantial impact on the likelihood that a household would be classified as poor, was the floor area per capita. The other three variables were not statistically significant, namely floor type, wall type, and roof type. In addition, the elimination of the physical type of house would reduce the Area Under the Curve of the RE-WLR and EFWLR methods by 6.78 percent and 6.85 percent, respectively.